Co‐occurrence of high densities of brown hyena and spotted hyena in central Tuli, Botswana - Vissia, S.; Wadhwa, R.; Langevelde, F. (Journal of zoology (1987), 2021)
Large carnivore populations are declining worldwide due to anthropogenic causes such as habitat loss and human expansion into wild areas. Competition between large carnivores can exacerbate this decline. While brown hyena Parahyaena brunnea and spotted hyena Crocuta crocuta belong to the same family, they are rarely found in the same area or co‐occur at low densities as spotted hyena are known to exclude brown hyena. In Central Tuli, Botswana, however, brown hyena and spotted hyena are both found at high densities. We undertook a camera trap survey in this area to estimate the densities of both species, and to examine temporal overlap and co‐detection patterns of brown and spotted hyena. Estimated population densities based on spatial capture–recapture models were 10.5 ± 1.9/100 km2 for brown hyena and 14.9 ± 2.2/100 km2 for spotted hyena. These population densities are among the highest reported estimates in southern Africa. Strong temporal overlap was found between brown and spotted hyena, while there was no decrease in detection rate of brown hyena at camera sites where spotted hyena were also detected, which indicates that both hyena species did not tend to avoid encounters. Although both species compete for the same prey, we suggest as possible explanations that prey densities are high and that competition does not significantly negatively impact brown hyena, because brown hyena is a scavenger whereas spotted hyena scavenge and kill prey. With the found high densities of both carnivores, this study adds to the known variation in composition of existing large carnivore communities and suggests testable explanations for these densities. Brown hyena and spotted hyena are rarely found in the same area or they co‐occur at low densities, however in central Tuli, Botswana, both are found at high densities. In this study, we estimated densities of both hyenas and examined their temporal overlap and co‐detection patterns. Estimated population densities based on spatial capture‐recapture models were 10.5 ± 1.9/100 km2 for brown hyena and 14.9 ± 2.2/100 km2 for spotted hyena, which are amongst the highest estimates for these species in southern Africa. We found strong temporal overlap between both species while brown hyena detection rate was unaffected by spotted hyena detection rate, indicating both hyena species did not tend to avoid encounters.